Cultural Literacy in the Era of Society 5.0 through Transformative Learning of Indonesian Language and Literature - Yuni Suriyanti; Rahmi Izzati; Alfiaturrahmi; Sarima Lestari; Lina Sundana; Isfiana Nursari; Novi Diana (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
The learning of Indonesian Language and Literature plays a strategic role in fostering students’ cultural literacy amid the challenges of globalization and the crisis of cultural identity. This article discusses how a transformative learning approach can instill cultural values through reflective and contextual educational processes. Using a library research method and qualitative descriptive analysis, this study finds that cultural literacy can be strengthened through students’ engagement in critical reading, intercultural dialogue, and the production of literary works that reflect local values. Transformative learning not only enhances language competence and literary appreciation but also reinforces students’ national identity and tolerance